1999
DOI: 10.1110/ps.8.11.2487
|View full text |Cite
|
Sign up to set email alerts
|

Locating and identifying posttranslational modifications by in‐source decay during MALDI‐TOF mass spectrometry

Abstract: A technique is described for identifying and locating posttranslational modifications (PTMs) in peptides and proteins of known sequence by interpretation of c(n) ion signals generated by in-source decay during delayed ion extraction in matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Sites of phosphorylation in seven synthetic peptides were determined, as was the location of both the heme group and N,N,N-trimethyllysine in yeast cytochrome c. A semi-automated data analysis process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…Moreover, PTMs that do not interfere with the ISD fragmentation of the peptide backbone can be studied by ISD as well. For example, Lennon et al demonstrated in 1999 that labile modifications such as serine phosphorylations were not affected by the ISD process [49]. These PTMs can therefore be characterized either by a direct MALDI-ISD experiment or after a pMS 3 -sequencing methodology [50].…”
Section: Maldi-isd and Ptmsmentioning
confidence: 99%
“…Moreover, PTMs that do not interfere with the ISD fragmentation of the peptide backbone can be studied by ISD as well. For example, Lennon et al demonstrated in 1999 that labile modifications such as serine phosphorylations were not affected by the ISD process [49]. These PTMs can therefore be characterized either by a direct MALDI-ISD experiment or after a pMS 3 -sequencing methodology [50].…”
Section: Maldi-isd and Ptmsmentioning
confidence: 99%
“…This pathway would not be theoretically limited by the mass of the analyte, thus allowing ISD to be used to sequence large proteins. Moreover, it was demonstrated that during radical-induced ISD and just like ETD or ECD, posttranslational modifications are preserved, including labile ones such as phosphorylation [19][20][21]. Nevertheless, since radical-mediated ISD is a reductive reaction, disulfide bonds could be altered [22], and information concerning their position could be lost.…”
Section: Introductionmentioning
confidence: 99%
“…61,62) erefore, MALDI-ISD can be used for the topdown sequencing of unknown and post-translational modied proteins. 8,[21][22][23][24][25][26][27][28][29][30]61,62) It should be stressed that the model for MALDI-ISD was constructed on the basis of X-ray crystallography ndings and SPM analyses of matrix crystals, as well as the use of isotope-labelled peptides.…”
Section: Resultsmentioning
confidence: 99%
“…19) ey reported the observation of unusual fragment ions c and z+2 assigned by Biemann's nomenclature. 20) Subsequently, several groups reported on the MALDI-ISD data of peptides and proteins from the standpoints of practical, 8,[21][22][23][24][25][26][27][28][29][30] basic [7][8][9][10][31][32][33] and review interests, 34) as summarized in Table 1. Recent advances in the fragmentation and theoretical considerations of MALDI-ISD have been reviewed by Asakawa 35) and Moon et al 36) We also found fragment ions c and z+2 re ecting the amino acid sequence in a MALDI mass spectrum of angiotensin I independent of Brown and Lennon's report, 6) in the course of experiments directed at the in uence of laser uence on the appearance and peak resolution of an analyte signal [A+H] + in the late 1997s.…”
Section: Discovery Of Maldi-isd Phenomenon and Early Research Publicamentioning
confidence: 99%